Impact of TNFAIP3 Genetic Polymorphisms on Primary Immune Thrombocytopenia in Egyptian Adults: Case-control Study - Zanaty , Mohamed; Korayem, Osama; Meabed, Mohamed H.; El Demerdash, Doaa; Abdelghany, Wafaa M. (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Immune Thrombocytopenia (ITP) is a common acquired hematological disease. Genetic polymorphisms play an important role in ITP pathogenesis and prognosis. TNF-α-induced protein 3 (TNFAIP3) is a negative regulator of NF-kB in many signaling pathways. Several variants of TNFAIP3 have been associated with various inflammatory autoimmune disorders. AIM: Our study aimed to study the association of TNFAIP3 single nucleotide polymorphisms (SNPs); rs2230926 & rs5029939 with ITP susceptibility, as well ITP prognosis by follow up the cases for 18 months. METHODS: One hundred and ten ITP patients as well 110 matched unrelated normal controls were enrolled in our study. The polymorphisms were assessed by real-time polymerase chain reaction (real time PCR). RESULTS: There were a significant difference between cases and control groups regarding rs2230926 T>G and rs5029939 C>G frequencies with p < 0.05. Linkage disequilibrium (LD) analysis of the two variants revealed that there was a significant LD (p < 0.001). Non-cutaneous bleeding manifestations were observed mainly in the mutant genotypes of rs2230926 and rs5029939. The ITP patients with mutant genotypes of rs5029939 showed more need to use 2nd line immunosuppressive therapy as well the mutant genotypes of rs2230926 showed more steroid dependence and less complete recovery. CONCLUSION: Our data concluded the presence of LD between rs5029939 and rs2230926. The mutant genotypes of both variants were associated with increase the susceptibility to ITP and accompanied by worse clinical manifestations and poor response to the treatment in the adult Egyptian patients.